The Chicago Blackhawks : greatest sports business turnaround ever? - Shein, James B., 1942- (SAGE knowledge. Cases., 2016)
This case explores the turnaround and corporate renewal of the Chicago Blackhawks professional hockey team, which transformed from one of the worst-run organizations in all of professional sports in 2007 to one that won the Stanley Cup in 2010.